2020
DOI: 10.1002/hbm.25265
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity between bed nucleus of the stria terminalis and amygdala: Reproducibility and relation to anxiety

Abstract: In a previous study, we investigated the resting‐state fMRI effective connectivity (EC) between the bed nucleus of the stria terminalis (BNST) and the laterobasal (LB), centromedial (CM), and superficial (SF) amygdala. We found strong negative EC from all amygdala nuclei to the BNST, while the BNST showed positive EC to the amygdala. However, the validity of these findings remains unclear, since a reproduction in different samples has not been done. Moreover, the association of EC with measures of anxiety offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Their findings indicated that both high‐level cognitive networks and low‐level perceptual networks could contribute to estimating anxiety behaviors by their static functional profiles. Static effective connectivity studies further revealed abnormal effective connectivity associated with the amygdala, supporting a dysregulation of core structures in the affect control network of anxiety (Hofmann & Straube, 2021 ; Liao, Qiu, et al, 2010 ; Qiao et al, 2017 ). However, even in the resting state, the functional brain networks show significant time variability and dynamic reconstruction (Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Their findings indicated that both high‐level cognitive networks and low‐level perceptual networks could contribute to estimating anxiety behaviors by their static functional profiles. Static effective connectivity studies further revealed abnormal effective connectivity associated with the amygdala, supporting a dysregulation of core structures in the affect control network of anxiety (Hofmann & Straube, 2021 ; Liao, Qiu, et al, 2010 ; Qiao et al, 2017 ). However, even in the resting state, the functional brain networks show significant time variability and dynamic reconstruction (Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 93%
“…The changes in effective connectivity patterns in emotional regulation regions may reflect directional neural communications, which provide deeper insights into anxiety (Hofmann & Straube, 2021). It is well known that the brain is highly dynamic rather than static.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, intense stress can hyperactivate the LC that is associated with anxiety (Borodovitsyna et al, 2018;Morris et al, 2020) due to limbic dysregulation (e.g., Herman et al, 2005). In particular, it is related to the functional connectivity between the bed nucleus of the stria terminalis (BNST) and amygdala (e.g., Clauss, 2019;Knight and Depue, 2019;Hofmann and Straube, 2021). The nuances are that the amygdala is involved in explicit threat processing (i.e., threat confrontation), whereas the BNST is involved in ambiguous threat processing (i.e., threat anticipation; Herrmann et al, 2016;Klumpers et al, 2017;Naaz et al, 2019; see also Fox et al, 2015;Fox and Shackman, 2019;Luyck et al, 2019).…”
Section: Alarm-to-threat (Check) Stagementioning
confidence: 99%
“…The stria terminalis connects the BNST to the amygdala by a C-shaped course (Kamali et al 2015 ; Dzafic et al 2019 ; Hofmann and Straube 2021 ). Direct projections were also detected from the occipital cortex to the BNST in the human brain (Catani et al 2003 ; Avery et al 2014 , Kamali et al 2020b ).…”
Section: Introductionmentioning
confidence: 99%